2018
DOI: 10.1038/s41598-018-24389-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assistant Diagnosis for Electronic Medical Record Based on Convolutional Neural Network

Abstract: Automatically extracting useful information from electronic medical records along with conducting disease diagnoses is a promising task for both clinical decision support(CDS) and neural language processing(NLP). Most of the existing systems are based on artificially constructed knowledge bases, and then auxiliary diagnosis is done by rule matching. In this study, we present a clinical intelligent decision approach based on Convolutional Neural Networks(CNN), which can automatically extract high-level semantic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 38 publications
0
48
0
Order By: Relevance
“…Deep learning has made significant improvement in research and started to make changes in our daily lives. In the medical field, many studies have applied deep learning and shown many great successes [78,[113][114][115][116][117][118][119][120][121]. One advantage of using deep learning to train a model is its capability to continue training when more data is available [27].…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…Deep learning has made significant improvement in research and started to make changes in our daily lives. In the medical field, many studies have applied deep learning and shown many great successes [78,[113][114][115][116][117][118][119][120][121]. One advantage of using deep learning to train a model is its capability to continue training when more data is available [27].…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…Finally, the output y is sent to the Softmax classifier to obtain a predicted value for each health indicator [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…In order to improve the efficiency of multiple convolutional networks, it is also possible to more directly simulate the dependence of adjacent tags in the segmentation, so that the final prediction energy can be Influenced by the model's value on nearby tags, this DCNN uses a cascade structure to implement the output of the first convolutional network as an additional input to the second convolutional network. At the same time, in order to enable DCNN to train more effectively, a residual connection can be used, that is, an independent connection bypassing the parameter layer is created in the network [14]. The convolutional layer involves three tensors: two feature maps and one convolution kernel, as in equation 1:…”
Section: Frame Of Image Segmentation Processing Based On Dcnn Algmentioning
confidence: 99%